Morphotype and caloric ingestion and its relationship with the physical performance of Mexican boxers - Castro-Zamora, A. A.; Borbon-Castro, N. A.; Cruz-Castruita, R. M.; de la Cruz-Ortega, M. F.; Lopez-Garcia, R. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2024)
Background. Boxing is a sport that generates important morpho-physiological adaptations in boxers, requiring physical monitoring from the beginning of sports preparation. Aim. the objective of this study is to correlate physical performance with morphotype and caloric intake in Mexican boxers during physical preparation and compare them by amateur and professional group. Methods. Quantitative, cross-sectional and comparative study carried out in August 2016 in a sample of 24 male boxers (16 amateurs and 8 professionals) participated, age 18.37±4.60 years, body weight 59.89±10.20kg and height 168.92±8.32cm. During physical preparation, body composition was evaluated with the pentacompartmental model, somatotype, caloric ingestion through 24-hour reminders (R24Hr) and physical performance. Results. significant differences (p<0.05) were found in muscle mass, mesomorphic and ectomorph somatotypes, relative and absolute VO2max and caloric protein ingestion. A predominance of the ectomorph-mesomorphic somatotype was observed in amateurs and balanced mesomorph in professionals, and a negative correlation of relative VO2max with adipose mass (r=-0.631; p=0.001) and positive with muscle mass (r =0.503; p=0.012), in addition the absolute VO2max shows a positive correlation with muscle mass (r=0.470; p=0.020), the mesomorphic somatotype (r=0.533; p=0.007) and negative with the ectomorph (r=-0.415; p=.044), also positive correlation with protein intake in calories (r=0.523; p=0.010). Conclusion. both groups of boxers presented an adequate morphotype, body composition and caloric ingestion for the sports level, type of preparation and training stage they performed during the intervention, positively influencing physical-sports performance.